Liparis wenshanensis, a new orchid species from China: Evidence from morphological and molecular analyses - Su, Yong-Yu; Huang, Yi-Lang; Chen, Li-Jun; Zhang, Pei-Wen; Liu, Zhong-Jian; Zhang, Guo-Qiang (Phytotaxa, 2015)
A new orchid species, Liparis wenshanensis, discovered in Yunnan, China is described and illustrated in this study based on morphological and molecular analyses. A detailed comparison between the newly discovered orchid and other members of the genus, Liparis, was conducted. The new plant is characterized by the combination of the following features: a long rachis with 45 to 55 flowers; white sepals, petals and column; a greenish lip with a purplish center; strongly recurved and revolute dorsal sepals and petals; strongly recurved, oblong lateral sepals; a cordate lip that is strongly deflexed below the middle, with a two-lobed apex and a two-lobed callus at the base; an arcuate column with a lamella extending along the center almost to the stigma, and with a pair of broad wings toward the apex. These features distinguish the new orchid from all other known species of Liparis. We proceeded to a phylogenetic analysis to ascertain the systematic position of this enigmatic species. Molecular analyses based on nuclear ribosomal ITS and plastid matK DNA sequence data supports the recognition of L. wenshanensis as a distinct species.